Environmental Accountability or Symbolic Compliance? A Critical Review of ESG Ratings, Greenwashing, and Indirect Emissions in the Global Insurance Sector - Patyrykin, Kirill; Vasyukova, Lyudmila (International Journal of Energy Economics and Policy, 2025)
The increasing visibility of the Environmental, Social, and Governance (ESG) models has altered the demands of corporate sustainability, which makes ESG ratings one of the primary instruments that investors, regulators, and other stakeholders can use to evaluate environmental responsibility in any industry, the insurance sector being one of them. Peer-reviewed journals, working papers, regulatory reports, and NGO/industry publications were carefully chosen as sources of information to represent different academic, regulatory and practical views on the issue in question, covering 2010-2024. Through the analysis, the ESG theory, greenwashing theory, and institutional theory are combined to uncover the methodology inconsistencies, gaps in Scope 3 emissions reporting, and the predominance of hollow compliance. The analysis highlights the gap between declared sustainability performance and reality, especially in the area of indirect emissions of underwriting and investment activities, and greenwashing trends in the industry. The results indicate that ESG ratings often exaggerate the environmental responsibility of the insurers and include disclosure and governance rather than action in climate over substantive action of environmental accountability in financial intermediaries, and require a more stringent and comprehensive set of approaches to assessing environmental accountability of financial intermediaries.